1987
DOI: 10.1017/s026646230001117x
|View full text |Cite
|
Sign up to set email alerts
|

The Diffusion of Magnetic Resonance Imaging Scanners in a Changing U.S. Health Care Environment

Abstract: Technological aspects and early clinical experiences are arousing great enthusiasm over magnetic resonance imaging (MRI). However, influences such as regulation, reimbursement, and increasing competition also are playing important roles in determining the diffusion of this new technology. Of these considerations, competition among providers seems the most important. Competition related to MRI is manifested as direct competition over MRI services, using MRI to improve a provider's strategic position and competi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…In the past, opinion leaders wishing to be early acquirers have often posed the possibility of obtaining a competitive advantage as a rationale for assuming this risk. They properly argue that with medical technology, there is often a "first-mover advantage" [9]. By this they mean that a provider might gain organizational experience, name recognition, and a reputation for special expertise that will be hard for regional competitors to supersede when they later acquire the technology.…”
Section: Competition To Provide Clinical Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, opinion leaders wishing to be early acquirers have often posed the possibility of obtaining a competitive advantage as a rationale for assuming this risk. They properly argue that with medical technology, there is often a "first-mover advantage" [9]. By this they mean that a provider might gain organizational experience, name recognition, and a reputation for special expertise that will be hard for regional competitors to supersede when they later acquire the technology.…”
Section: Competition To Provide Clinical Servicesmentioning
confidence: 99%
“…For the reasons noted in the above paragraph, early acquisition has been a successful strategy for such previous imaging technologies as MRI [7,[9][10][11]. Nonetheless, there are some differences between molecular imaging and such technologies as MRI that might determine a different outcome.…”
Section: Competition To Provide Clinical Servicesmentioning
confidence: 99%
“…For example, Robinson and Luft (1985) characterized new service adoption as the result of a medical arms race, one that leads to inefficient investment in medical technology. Scholars later found evidence that the acquisition of new medical technology was driven by, among other factors, a hospital's attempt to maintain or expand a local market (Hillman et al, 1987) and the importance a hospital attaches to being a technological leader (Teplensky et al, 1995). Skinner & Staiger (2015, pg. 3) made progress in reconciling these views-that technology adoption led to improvements in health and that technology adoption was caused by, at least in part, nonmedical reasons-in arguing that health care "improvements are largely associated with the adoption of effective treatments, rather than more factor inputs per se.…”
Section: Introductionmentioning
confidence: 99%
“…To some extent, departments wishing early involvement in molecular im-aging can gain entrance at lower cost by focusing on rodent imaging. 6. Institutions most likely to be successful in establishing research programs are ones with a successful history in research and a diverse array of research resources at their institution outside of radiology.…”
Section: Critical Issues For Radiologymentioning
confidence: 99%
“…In the classical literature on the diffusion of medical technology, it is said that major innovations progressively diffuse from major academic medical centers to university-affiliated hospitals to community hospitals to outpatient centers and office practices and from urban to rural. However, studies of MR imaging showed a very different pattern of diffusion based on the medical economic environment of the times (5)(6)(7). Specifically, along with regulation, competition among providers played a major role in promoting the acquisition of MR imagers among atypical providers who either would ordinarily be expected to acquire technology later in the diffusion process or who had not previously been involved in medical imaging.…”
Section: Prospective View On the Diffusion Of Molecular Imagingmentioning
confidence: 99%